Multikulturalisme Pada Masa Dinasti Umayyah - Isma Aulia Zamaakh Syari; Meyniar Albina (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
The article was written with the aim of analyzing the state of multiculturalism during the Umayyad Dynasty. In Writing this article, the author uses a libraby research method with a descriptive analysis approach. By conducting this research, several results were obtained, including: (1) During the Umayyad Dynasty, many communities and community goups were found with diverse cultures and beliefs, (2) Arabization carried out by the Umayyad Dynasty made community groups with diverse tribes and beliefs become in the same language, (3) The policies carried out by the Caliphs provided many concessions to the Non-Muslim community.